A highly sensitive near-infrared luminescent metal–organic framework thermometer in the physiological range. Issue 53 (10th June 2016) - Zhao, Dian; Zhang, Jun; Yue, Dan; Lian, Xiusheng; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract : A highly sensitive, low toxic near-infrared luminescent metal–organic framework, Nd0.866 Yb0.134 BTB, was developed as a self-calibrated thermometer in the physiological range. Abstract : A near-infrared luminescent metal–organic frameworkNd0.866 Yb0.134 BTB was developed as a self-calibrated thermometer in the physiological range. Its features include high sensitivity and resolution, and good biocompatibility, making such a material useful for biomedical applications.